Strategi Penyusunan Business Plan UMKM Tas Lipat Ramah Lingkungan Lipatto Berbasis Business Model Canvas dan Inovasi Hijau - Ilma Puspanusa; Meriza Hendri (Universitas Nahdlatul Ulama Blitar, 2026)
This study explores the development strategy of Lipatto foldable bags using a design thinking approach to enhance product differentiation, competitiveness, and sustainability in the urban consumer market. The research aims to identify consumer needs, develop innovative product concepts, and assess the feasibility of integrating quality, aesthetics, eco-friendliness, and customization into a marketable product. Data were collected through structured observations, interviews, and market analysis in Bandung, followed by prototype development and consumer testing. The study employed Lean Canvas modeling to evaluate business feasibility and strategic positioning. Results indicate that consumers highly value multifunctional, durable, and aesthetically distinctive bags with eco-friendly materials and customizable features. The integration of design thinking stages empathize, define, ideate, prototype, and test enabled Lipatto to generate innovative solutions aligned with consumer expectations. Lean Canvas analysis demonstrated that the business model is viable, scalable, and adaptable for broader market segments. The findings provide practical implications for MSMEs in the creative industry seeking sustainable product innovation and strategic differentiation.